Representation of Beauty Standards in Two Selected Music Videos: Semiotic Analysis of Roland Barthes - Fajari, Alifia Salsabila; Kurniawan, Muhammad Hafiz (Modality Journal: International Journal of Linguistics and Literature, 2024)
Beauty standards are issues that still exist in society today. This issue of beauty standards is depicted in music videos entitled “Pretty Hurts” by Beyonce and “Mrs. Potato Head” by Melanie Martinez. In music video, there are signs used to communicate the meaning that can be analyzed using a semiotic approach to find out the meaning conveyed. The purposes of this research are to analyze denotation and connotation meaning of verbal and visual signs in both selected music videos, as well as the myth of beauty standards. Descriptive qualitative method is applied in this research to analyze the data which are in the form of screenshot of verbal and visual signs, while the method of collecting data used in this research is documentation. The data were taken from two selected music videos represent the issue of beauty standards. The total data of this research are 36 data, consisting of 9 data of verbal signs and 27 data of visual signs. The collected data were examined using Roland Barthes’ theory by analyzing the meaning of denotation and connotation, as well as the myth of beauty standards. The result of this study found the denotation and connotation meaning showed six features of beauty such as slim body, blonde hair, narrow face, large breast, white teeth, and fashionable appearance signify women’s beauty and represent attractiveness. Meanwhile, there are six myths of beauty standards found in two selected music videos such as ideal body, attractiveness, confidence, facial beauty, ideal face shape, and ideal beauty. Abstrak Standar kecancitkan merupakan sebuah fenomena yang masih terjadi di masyarakat kita saat ini. Permasalahan ini tergambar dari video musik yang berjudul “Pretty Hurts” karangan Beyonce dan “Mrs. Potato Head” karangan Melanine Martinez. Dalam video musik tersebut beberapa tanda digunakan untuk mengkomunikasikan makna yang dianalisis dengan pendekatan semiotika untuk menemukan makna yang dimaksud oleh Beyonce dan Melanie Martinez dalam lagu-lagunya. Tujuan penelitian ini adalah untuk menganalisis makna denotasi dan konotasi baik tanda verbal dan visual dalam kedua video music tersebut, beserta dengan analisis Myth mengenai standar kecantikan. Metode kualitatif deskriptif digunakan dalam penelitian ini untuk menganalisis data dalam bentuk hasil tangkapan layar dari video musik yang merepresentasikan isu standar kecantikan. Jumlah keseluruhan data dalam penelitian ini adalah 36 data yang meliputi 9 data tanda verbal dan 27 data tanda non-verbal atau visual. Data yang telah dikumpulkan kemudian dianalisis dengan menggunakan teori Roland Barthes yang meliputi analisis denotasi, konotasi, dan muth dari standar kecantikan. Hasil dari riset ini menemukan bahwa makna denotasi dan kontasi menunjukkan 6 fitur kecantikan yaitu badan yang langsing, rambut pirang, wajah yang proporsional, payudara yang besar, gigi yang putih dan penampilan yang menarik menjadi kunci dari kecantikan wanita dan merepresentasikan kecantikan yang memikat. Sedangkan dalam hal myth, penelitian ini menemukan bahwa tubuh yang ideal, kepercayaan diri, kecantikan wajah, bentuk wajah yang ideal dan kecantikan ideal merupakan wujud dari myth yang tengah dibangun dari video music tersebut. Kata Kunci: denotasi, konotasi, myth, standar kecantikan, video musik